Pengaruh Pandemic Covid -19 Terhadap Perilaku Manajemen Laba (Studi Empiris Pada Perusahaan Sub Sektor Hotel, Pariwisata, Restoran dan Retail) - Rahmat Fajar Ramdani; Dimas Pratomo; Ahmad Zuliansyah (ITB AAS INDONESIA, 2022)
This study aims to prove whether the COVID-19 pandemic has an effect on corporate earnings management behavior through an accrual approach which is analyzed through changes in discretionary values. accruals before and after the COVID-19 pandemic. The research sample consisted of 16 companies consisting of the hotel, tourism, restaurant and retail sub-sectors which were selected using the purposive sampling method. To analyze whether there is a significant difference in the value of discretionary accruals due to the COVID-19 pandemic, this study uses paired sample t - test analysis. The results of the study prove that empirically the covid -19 pandemic has no effect on earnings management behavior as evidenced by the absence of significant differences in the value of discretionary accruals before and after covid -19 in the hotel, tourism, restaurant and retail sub-sector companies. Keyword: manajemen laba dan discretionary accrual, non discretionary accrual, covid -19